2003
DOI: 10.1126/science.1078231
|View full text |Cite
|
Sign up to set email alerts
|

Toll Pathway-Dependent Blockade of CD4 + CD25 + T Cell-Mediated Suppression by Dendritic Cells

Abstract: Toll-like receptors (TLRs) control activation of adaptive immune responses by antigen-presenting cells (APCs). However, initiation of adaptive immune responses is also controlled by regulatory T cells (TR cells), which act to prevent activation of autoreactive T cells. Here we describe a second mechanism of immune induction by TLRs, which is independent of effects on costimulation. Microbial induction of the Toll pathway blocked the suppressive effect of CD4+CD25+ TR cells, allowing activation of pathogen-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
1,431
19
16

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,891 publications
(1,517 citation statements)
references
References 26 publications
51
1,431
19
16
Order By: Relevance
“…In addition to delivering MyD88-dependent signals typical of most TLRs, TLR-3 can also trigger a non-MyD88-dependent signaling pathway that induces secretion of type I interferons (11), which have been particularly implicated in the development of autoimmunity (13). Furthermore, we have shown that TLR-3 but not TLR-5 induces high levels of IL-6 secretion; this is notable because IL-6 can block the suppressor activity of CD4ϩ,CD25ϩ T cells (14).…”
Section: Discussionmentioning
confidence: 70%
“…In addition to delivering MyD88-dependent signals typical of most TLRs, TLR-3 can also trigger a non-MyD88-dependent signaling pathway that induces secretion of type I interferons (11), which have been particularly implicated in the development of autoimmunity (13). Furthermore, we have shown that TLR-3 but not TLR-5 induces high levels of IL-6 secretion; this is notable because IL-6 can block the suppressor activity of CD4ϩ,CD25ϩ T cells (14).…”
Section: Discussionmentioning
confidence: 70%
“…Studies have shown that TLR-activated DC can reverse Treg anergy, suggesting that this could override suppression and permit protective immunity towards pathogens [52,53] -10 [56]. This implies that microbial components are important to drive IL-10 production, which subsequently influence the development of regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, bacterial virulence factors from Bacillus anthracis impair in vivo DC function by disrupting intracellular signaling networks, thereby disarming adaptive immune responses [24]. On another level, TLR triggering on DC can block the suppressive effects of regulatory T cells by releasing specific cytokines [25]. It is possible that distinct TLR are triggered on DC by live and heat-killed bacteria.…”
Section: Discussionmentioning
confidence: 99%